The Need to Standardize the Criteria for Classifying Protected Areas within the EU - Dobrescu, Codruța Mihaela; Turtureanu, Anca; Popa, Ionuț; Dorobăț, Magdalin Leonard Dorobăț (Journal of Danubian Studies and Research, 2025)
Abstract: The European Union has paid increasing attention to the conservation of biodiversity in its member countries and to the protection of the environment. In this context, protected areas, regardless of their rank, surface area, geographical location, play an essential role in saving ecosystems and species in danger of extinction or simply threatened. However, despite their importance, a fundamental aspect of their management remains the non-uniformity in their classification and assessment in the Member States of the European Union and in other non-member European countries. The need to standardize the criteria for classifying protected areas has thus become a key theme in the debates on conservation. The implications are not limited to the effectiveness of environmental policies or the harmonization of standards between the different EU countries. The efficiency of national or EU funding for protected area officials could be greatly improved if there were a common denominator in classifying and comparing these protected areas. Each Member State adopts different rules and methodologies for identifying and designating protected areas, and this can lead to significant differences in the protection status of ecologically similar areas. For example, an area may be considered of major ecological importance in one country but not protected in another. A standardization of criteria would help to eliminate these discrepancies and provide a coherent and integrated approach to conservation. Bringing criteria to a common denominator could also facilitate the exchange of good practice between Member States, but also with EU neighbors and others aspiring to join. The different approaches adopted by each country, based on local or national conditions, can provide valuable lessons about what works and what does not work in nature conservation. However, without a common assessment basis, it is difficult to compare and apply these lessons on a large scale. By creating a common European framework, Member States could work together more effectively, pooling resources and experiences to protect areas of high ecological value. Another major argument for standardization is also the need to better comply with and implement European environmental legislation, in particular the Habitats Directive (92/43/EEC/21 May 1992) and the Birds Directive (2009/147/EC), which set the standard for ecological networks of protected areas, in particular the Habitats Directive (92/43/EEC/21 May 1992) and the Birds Directive (2009/147/EC) of the kind in the world. These directives require Member States to designate areas to protect habitats and to specify protected areas at European level. Different interpretations of these regulations can lead to discrepancies in their implementation, which undermines the effectiveness of these laws and compromises the objectives of nature protection. Another essential factor is the coordination and effective management of protected areas. If each country applies a different set of criteria and rules for the management of these areas, cross-border collaboration becomes complicated. Many of the protected areas in the European Union are located in the area that crosses national borders, and their inconsistent management can create confusion and delays in the implementation of protection measures. In conclusion, there are some unitary criteria for the classification of protected areas in the European Union is essential to ensure coherent, effective and integrated protection of biodiversity and to streamline management activities in this area, a more robust legislative framework could be achieved to protect biodiversity in the long term and ensure the sustainability of EU ecosystems. Kewords: protected areas, classification, standardization, UE